Intra-abdominal Candida spp infection in acute abdomen in a quality assurance (QA)-certified academic setting. Issue 7 (9th December 2016) - Rodolico, Vito; Di Carlo, Paola; Gulotta, Gaspare; D'Arpa, Francesco; Salamone, Giuseppe; Cocorullo, Gianfranco; Agrusa, Antonino; Giammanco, Anna; Sergi, Consolato
Abstract : Aims: To evaluate the contribution of light microscopy to detecting Candida spp infection in patients with complicated intra-abdominal infections (IAIs) admitted for acute abdomen to a quality assurance (QA)-certified surgical emergency ward. Methods: We conducted a retrospective study (2008–2012) of 809 abdominal intraoperative or biopsy tissue specimens obtained from patients admitted with acute abdomen and microbiological samples positive for Candida spp. Demographic data, mortality, comorbidities, specimen type, microscopy results, special histological staining performed, antimicrobial therapy were collected and analysed. Any comments at the multidisciplinary team meeting was recorded in minutes of and approved. Results: Sixty-six patients with complicated IAIs due to Candida spp were identified (39 male, 27 female, mean±SD age 75±20 years). Candida albicans was isolated in 35 cases and Candida non-albicans spp in 31 cases. Candida spp were isolated from blood in 50% of all selected microbiological specimens. Patients were stratified according to Candida spp (albicans vs non-albicans), underlying cancer disease and no previous antimicrobial administration, and a positive correlation with C. albicans isolation was found (p=0.009 and p=0.048, respectively). Out of 41 cases with microscopic evaluation, we identified yeast forms, pseudohyphae or both, indicative of Candida spp, in 23. Identification of Candida spp in histological specimens was higher in C. albicans cases than in C. non-albicans cases (73% vs 37.5%). Microscopy allowed prompt treatment of all patients. Conclusions: Light microscopy still has great diagnostic significance, being a solid QA step. It provides rapid information and clues in patients who may harbour impaired defence mechanisms, concurrent chronic conditions and/or cancer.